Human-centric lighting intelligence: A data-driven framework for multivariable response analysis and cluster-based prediction - Hyesung Cho; Ki Rim Kim; Kyung Sun Lee (Building and Environment, 2026)

Enhanced cellular uptake of sorafenib for hepatocellular carcinoma treatment: surface-modified PLGA nanoparticles with biomimetic alterations - Minki Jin; Jae Hyun Nam; Young-Guk Na; Taek Seon Yun; Bomin Song; Yu-Rim Hwang; Hong-Ki Lee; Jong-Suep Baek; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2025)

Potential generation and consumption of carbon dioxide during treatment of mine drainages in South Korea - Duk-Min Kim; Ki-Rim Lee; Mi-Sun Park (Science of The Total Environment, 2025)

Assessing seepage sources of a tailings dump and fractionation of Mo and Zn isotopes - Duk-Min Kim; Dae-Gyu Im; Hye-Lim Kwon; Seong-Taek Yun; Ki-Rim Lee; Mi-Jeong Park; Mi-Sun Park (Science of The Total Environment, 2025)

Safety of applying influenza-antigen-coated microneedles to rat skin and the antigen specific immune response in vivo - Taek-Seon Yun; Bomin Song; Yu-Rim Hwang; Minki Jin; Hyeseung Seonwoo; Donki Kim; Hye Won Kim; Byeong Cheol Kim; Daekyung Kim; Boyeong Park; Jeong Yeon Kang; Seung-Ki Baek; et al. (Journal of Pharmaceutical Investigation, 2024)

Considerations related to the in-use stability of sterile pharmaceutical dosage forms - Hyelim Yoo; Young-Guk Na; Minki Jin; Jong-Hee Won; Bomin Song; Taek-Seon Yun; Yu-Rim Hwang; Hong-Ki Lee; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2024)

An economically advantageous amorphous solid dispersion of the fixed combination of lopinavir and ritonavir - Taek-Seon Yun; Minwoo Jung; Ki-Hyun Bang; Hong-Ki Lee; Minki Jin; Hyelim Yoo; Jong-Hee Won; Bomin Song; Yu-Rim Hwang; Jong-Suep Baek; Cheong-Weon Cho (Journal of Pharmaceutical Investigation, 2023)

Complete genome sequence of cnidium virus 2, a novel cytorhabdovirus isolated from Cnidium officinale in South Korea - Yang Chan Park; Kwang-Kyu Kim; Hyun Jeong Jun; Eun-Ha Kang; Su-Rim Lee; Jun Ki Ahn; Han Kyu Seo; Su-Heon Lee; Kwang-Lae Hoe (Archives of Virology, 2023)

Complete genome sequence of a novel member of the genus Polerovirus from Cnidium officinale in South Korea - Yang Chan Park; Kwang-Kyu Kim; Hyun Jeong Jun; Eun-Ha Kang; Su-Rim Lee; Jun Ki Ahn; Han Kyu Seo; Su-Heon Lee; Kwang-Lae Hoe (Archives of Virology, 2023)

Correction to: Improved Dust Detection over East Asia Using Geostationary Satellite Data - Yu-Rim Shin; Eun-Ha Sohn; Ki-Hong Park; Geun-Hyeok Ryu; Soobong Lee; Seon-yong Lee; Na-Yeon Park (Asia-Pacific Journal of Atmospheric Sciences, 2021)

Improved Dust Detection over East Asia Using Geostationary Satellite Data - Yu-Rim Shin; Eun-Ha Sohn; Ki-Hong Park; Geun-Hyeok Ryu; Soobong Lee; Seon-Young Lee; Na-Yeon Park (Asia-Pacific Journal of Atmospheric Sciences, 2021)
This paper presents an improved algorithm, based on the D*-parameter, for dust detection over the East Asian region using brightness temperature differences (BTDs) between the infrared channels of the Advanced Himawari Imager (AHI) onboard Himawari-8. The developed algorithm defines a dust index in the form of the ratio of BTDs: BTD between the 10.4 μm and 12.4 μm channels (BTD 10.4–12.4 ) to that between the 8.6 μm and 10.4 μm channels (BTD 8.6–10.4 ). To identify dust with this index, threshold values were determined empirically. A masking technique using the BTD 8.6–10.4 was utilized in the dust index to mitigate the problem of detecting clear-sky deserts and fog over the ocean as dust. BTD 8.6–10.4 was analyzed for dust, clear-sky desert, and fog over the ocean cases during 2017 and 2018 with this method. Fog over the ocean and clear-sky desert were distinguished by the criteria of BTD 8.6–10.4 > −1.1 K and BTD 8.6–10.4 > −1 K, respectively. Based on these thresholds, the influence of fog over the ocean and clear-sky desert was filtered out. The results showed that the dust area was qualitatively consistent with RGB images and ground observation data. Comparison with the AERONET aerosol optical depth (AOD) demonstrated that the D*-parameter was exponentially proportional to AOD, and the correlation coefficient between them was approximately 0.6. The improved Asian Dust detection algorithm can be applied to the monitoring of dust dispersion and movement and also serve as a quantitative indicator of Asian Dust.

Optimal Condition of Isolation from an Adipose Tissue-Derived Stromal Vascular Fraction for the Development of Automated Systems - Su Jin Lee; Chae Rim Lee; Ki Joo Kim; Yeon Hee Ryu; Eunjin Kim; Yu Na Han; Suk-Ho Moon; Jong-Won Rhie (Tissue Engineering and Regenerative Medicine, 2020)

Nobiletin improves emotional and novelty recognition memory but not spatial referential memory - Jiyun Kang; Jung-Won Shin; Yoo-rim Kim; Kelley M. Swanberg; Yooseung Kim; Jae Ryong Bae; Young Ki Kim; Jinwon Lee; Soo-yeon Kim; Nak-Won Sohn; Sungho Maeng (Journal of Natural Medicines, 2017)

Enhanced production of resveratrol derivatives in tobacco plants by improving the metabolic flux of intermediates in the phenylpropanoid pathway - Yu Jeong Jeong; Chul Han An; Su Gyeong Woo; Ji Hye Park; Ki-Won Lee; Sang-Hoon Lee; Yeonggil Rim; Hyung Jae Jeong; Young Bae Ryu; Cha Young Kim (Plant Molecular Biology, 2016)

The role of APCDD1 in epithelial rearrangement in tooth morphogenesis - Sanjiv Neupane; Wern-Joo Sohn; Gi-Jeong Gwon; Ki-Rim Kim; Sanggyu Lee; Chang-Hyeon An; Jo-Young Suh; Hong-In Shin; Hitoshi Yamamoto; Sung-Won Cho; Youngkyun Lee; Jae-Young Kim (Histochemistry and Cell Biology, 2015)